Pengaruh Supervisi Akademik dan Budaya Sekolah Terhadap Kinerja Mengajar Guru - Mabruroh, Mabruroh; Suryapermana, Nana; Suryana, Atang (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2021)
This study aims to: 1) determine the relationship between the principal's academic supervision and teacher performance at SKh N 02 Serang City; 2) Knowing the relationship of school culture with the teaching performance of teachers in SKh N 02 Serang City; 3) Knowing the relationship between academic supervision and culture in schools in SKh N 02 Serang City; 4) Knowing the relationship between academic supervision and school culture together with the teaching performance of teachers in SKh N 02 Serang City. Research with quantitative methods, the analysis technique used is simple and multiple correlation, simple regression analysis and multiple regression. The population as well as the research sample are SKh N 02 Serang teachers, totaling 40 people. The research instrument used a questionnaire on academic supervision, school culture and teacher teaching performance. The results of the study obtained a significant influence between academic supervision and school culture on the teaching performance of teachers.